ANALISIS SYSTEM PEMBERIAN KOMPENSASI DAN FAKTOR-FAKTOR YANG MEMPENGARUHI PADA BANK BRI (Studi Kasus Pada Bank BRI Cabang Makassar) - Sri Rahayu Indah Samputri; St. Haerani St. Haerani; Erlina Pakki; Andi Sugeng Sapta Aji (AkMen JURNAL ILMIAH, 2015)
This study aimed to analyze the system of compensation and determine the factors that influence the BRI bank branch Makassar. The research data was obtained from interviews and direct observation with several parties related to the compensation of employees. The study's findings indicate that the compensation system used by the Makassar branch of BRI bank is the payroll data inputted by the human resources department and then classified into a data base salary then distributed through direct employee accounts. Magnitude of the amount of compensation is determined based on three (3) main things which grade / position, length of service and level of education which is owned by the employee. Factors that influence the amount of compensation is based on company profits, unions, government, contributions occupation, work experience, expertise, performance or achievements.